(In)sustentabilidade das políticas territoriais na microrregião de Estância/SE : uma análise com indicadores socioambientais - Sampaio, Renata Maria de Almeida (2015)
A key challenge for public policy is the need to make productive activities effectively contribute to the improvement of living conditions of the population and protect the biogenetic heritage to be passed on to future generations. Therefore, such discussions were analyzed by socio-environmental indicators feature aimed at analyzing the (un) sustainability of territorial policies in the micro resort, Sergipe. The proposed analysis was carried out according to the selection of environmental indicators that showed the socio-institutional, environmental and spatial dimensions. The indicators were verified from the use of secondary information, providing conditions for an analysis jointly appointed by indicators of overall progress towards sustainability. The survey revealed the need to establish paths for those interested in developing improvements in the municipalities of Estancia micro due to demands unmet satisfactorily having regard to the results of the policies installed in this territory. According to the results presented to the socio-institutional dimension, the variables related to Education and Social Vulnerability can be highlighted as the most negative values in the performance scale, with significant percentages with regard to vulnerable poverty population in all municipalities studied .